Analisis Pengaruh Pertumbuhan Ekonomi (PDRB), Rata-Rata Lama Sekolah Dan Pengangguran Dalam Disparitas Anggaran Pendidikan Di Indonesia Tahun 2015-2019 - Luthfiah Azizah (Universitas Negeri Padang, 2021)
In the field of education every human being will experience a process. The presses are made to improve science, ability, creativity and innovation. In addition, education is able to increase economic growth, with the education sector able to increase the quality of human resources on the other hand indirectly, the old school's average increase in the quality of human resources and labor productivity so that it can reduce unemployment. The study aims to find out the impact of economic growth, the average length of school and unemployment on Indonesia's provincial education budget 2015-2019. This kind of research uses a quantitative method with the fixed effect model. The results of variable economic growth has significant impact on the education budget with a probability of 0,0019 or less than 0,05, for the average variable old school has significant impact on the education budget with a probability of 0.0022 and unemployment variable have a staggering 0.0000 or less than 0,05, and a variables of economic growth, the average long school and unemployment have a significant impact on the education budget with a probability of 0.000009 or less than a 0.05.